Consensus-based development and practice testing of a generic quality indicator set for parenteral medication administration at home: a RAND appropriateness method study - Gréanne Leeftink; Anke Lenferink; Jedidja Lok-Visser; Roald Hunneman; Cecile H J Bekkers; P Margreet G Filius; Jan Gerard Maring (BMJ Open, 2025)
Objectives Due to nursing shortages, an ageing population and increasing care demand, there is a growing interest in parenteral medication administration at home (PMAaH), comprising the administration of parenteral medication in the home situation of patients. The operational design of such PMAaH care pathways is complex, resulting in many variations of adoptions, showing a need for a quality framework. Although quality indicators (QIs) have been proposed to monitor the quality of specific care pathways, a generic quality framework for all types of PMAaH is lacking. Therefore, this study proposes a generic quality set for PMAaH, which includes structure and process QIs, to benchmark and redesign PMAaH care pathways to ensure high quality.Design A generic QI set was developed for PMAaH using a systematic RAND appropriateness method adapted at the third phase. This method consisted of a scoping review to identify indicators, an expert panel rating phase including an online questionnaire and subsequent panel meeting to assess the appropriateness of the indicators and a retrospective practice testing to evaluate the feasibility, clarity and measurability of the indicators. After the practice testing, which consisted of an online questionnaire where experts could indicate the implementation state of all indicators in their hospital, a third expert panel adjusted the set to increase the likelihood of implementation in practice.Setting The experts, all healthcare professionals involved in PMAaH processes, were recruited using the snowball sampling technique from three large Dutch, teaching hospitals. Subsequently, a practice testing by self-assessment was conducted in seven large Dutch teaching hospitals.Participants 17 and seven healthcare professionals with diverse backgrounds participated in the online questionnaire and panel meeting, respectively.Results The scoping review resulted in 36 QIs for PMAaH. After two expert panel rating rounds (online questionnaire and panel meeting), two indicators were removed: a QI related to travel distance policy since it was irrelevant and redundant, and a QI stating that a clinician should take the lead in a PMAaH-team, which was deemed too restrictive. After the practice testing, two QIs were removed: a QI related to clinical response documentation, which was unclear for the practice testing respondents and already covered by other QIs, and a QI related to survival documentation, which was deemed infeasible and undesirable to measure this differently than other patients by the third expert panel.The final set consists of 32 indicators (of which 15 were structure indicators and 17 were process indicators). The final set predominately includes QIs that are aimed at patient safety but also QIs focusing on the working conditions of the healthcare workers. 17.6% of the QIs are currently fully implemented in general in all seven hospitals. The practice testing revealed that operational QIs are more frequently implemented in practice than systemic QIs and that a structured quality assurance programme is needed in the hospitals.Conclusions This study proposes a generic quality set for PMAaH that hospitals can use to redesign and benchmark PMAaH care pathways to assure high quality. The practice testing confirmed that there is a need for this structured quality set.